A new approach for calculating microalgae culture growth based on an inhibitory effect of the surrounding biomass - Jung, Sun-Hwa; Mchardy, Christopher; Rauh, Cornelia; Jahn, Alexander; Luzi, Giovanni; Delgado, Antonio; Buchholz, Rainer; Lindenberger, Christoph (Bioprocess and Biosystems Engineering, 2021)
Ever since the potential of algae in biotechnology was recognized, models describing the growth of algae inside photobioreactors have been proposed. These models are the basis for the optimization of process conditions and reactor designs. Over the last few decades, models became more and more elaborate with the increase of computational capacity. Thus far, these models have been based on light attenuation due to the absorption and scattering effects of the biomass. This manuscript presents a new way of predicting the apparent growth inside photobioreactors using simple models for enzymatic kinetics to describe the reaction between photons and the photosynthetic unit. The proposed model utilizes an inhibition kinetic formula based on the surrounding biomass to describe the average growth rate of a culture, which is determined by the local light intensities inside the reactor. The result is a mixed-inhibition scheme with multiple inhibition sites. The parameters of the new kinetic equation are replaced by empirical regression functions to correlate their dependency on incident light intensity and reactor size. The calibrations of the parameters and the regression functions are based on the numerical solutions of the growth rate computed with a classical Type II model. As a final verification, we apply the new equation in predicting the growth behavior of three phototrophic organisms in reactors of three different sizes.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Algae cultivation; Growth kinetics; Inhibitory effects; Numerical methods

Asymptotic analysis of flow processes at drawing of single optical microfibres - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Fujimoto Meinecke, Ken; Rauh, Cornelia; Delgado, Antonio (International Journal of Chemical Reactor Engineering, 2011)
Microstructured optical fibres (i.e. fibres that contain holes) have assumed a high profile in recent years, and given rise to many novel optical devices. The problem of manufacturing such fibres by heating and then drawing a preform is considered for both the cases of annular microfibres and annular capillaries. A fluid-mechanics model suggested in literature that uses asymptotic analysis based on the small aspect ratio of capillaries is analysed and revised. The leading-order equations are examined in some asymptotic limits, many of which give valuable practical information about the control parameters that influence the drawing process. Additionally, the solution obtained for a single capillary provides a suitable basis for describing more complicated fibre structures. Copyright © 2011 The Berkeley Electronic Press. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.asympt
Keywords: asymptotic analysis; holey fibre; microstructured optical fibres; numerical efforts; photonic crystal fibres

Comparison between an analytical asymptotic fiber drawing model with full Navier-Stokes solution taking into account the effects of inner pressure and surface tension - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Fujimoto Meinecke, Ken; Rauh, Cornelia; Delgado, Antonio (Journal of Lightwave Technology, 2011)
A fluid-mechanics model that make use of asymptotic analysis based on small aspect ratio of capillaries has been compared with the full 3-D set of the N.-St. equations, for modelling the fabrication of capillary tubes. The final asymptotic equations are solved numerically and then compared with the N.-St. solutions, obtained with a commercial finite elements solver. The present paper focuses on the comparison of the solution of the two methods taking into account the effects of surface tension and internal hole pressure, since those are of essential importance during drawing. It is shown that the analytical asymptotic method delivers reliable results for practical applications, as long as the inner pressure or the temperature does not exceed too high values. © 2011 IEEE.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.compar
Keywords: Asymptotic analysis; holey fibres; mathematical modelling; microstructured optical fibres (MOFs); numerical methods; photonic crystal fibres

Comparison between different strategies for the realization of flashing-light effects - Pneumatic mixing and flashing illumination - Luzi, Giovanni; McHardy, Christopher; Lindenberger, Christoph; Rauh, Cornelia; Delgado, Antonio (Algal Research, 2019)
A major limitation for the phototrophic cultivation of microalgae in photobioreactors is the low culture density which results in expensive harvesting and downstream processes. It is often mentioned that intensive mixing of the culture can improve the efficiency of light utilization by realizing flashing-light effects which enhance the growth of cell cultures. Alternatively, flashing light sources could provide a way to realize this effect without the need of supplying additional energy for fast mixing. While the effects of mixing have been investigated at various reactor scales, experiments with flashing illumination have been mostly conducted in small geometries. In addition, few studies have been conducted for photobioreactors with larger light paths, being characteristic for the production scale. By means of numerical simulations, we evaluate pneumatic mixing and flashing illumination with regard to their ability to realize flashing-light effects in a 5 cm diameter bubble column filled with a suspension of Chlamydomonas reinhardtii. To the best of our knowledge, a numerical comparison between the effects of flashing illumination and pneumatic mixing on the culture growth has not been reported in literature.
CRIS-Team WoS Importer:2019-02-22

Comparison of different software for the computation of multiphase flow in photobioreactors. - Luzi, Giovanni; McHardy, Christopher; Lindenberger, Christoph; Rauh, Cornelia; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
Bubble column bio-reactors, numerical simulations, computational Fluid Dynamics Abstract Nowadays a potential choice for a sustainable production of food, feed or fuels is represented by microalgae. The cultivation of these microorganisms often occurs in photobioreactors (PBR) where the maximum allowable culture density is limited to few grams per liters. Enhancing the pneumatic mixing or utilizing different illumination strategies can potentially increase the PBR productivity. In our recent contribution, we compared pneumatic mixing and flashing light illumination with respect to their ability to promote flashing light effects in a 5 cm diameter bubble column PBR. The outcome of our study clearly indicates that at the investigated operating conditions pneumatic mixing alone has no impact at all on the growth rate. In contrast, numerical simulations show that illumination with flashing LED leads to an increase of the growth rate up to a factor of 2.5 at flashing frequencies higher than 50 Hz. Our numerical work has been conducted with two commercial software, i.e. ANSYS CFX ® and Matlab ®. The former one is costly and does not allow much flexibility to modify the source code. In the present contribution, we compare the CFD results for the multiphase flow obtained with ANSYS CFX ® and OpenFOAM ® , which is a non-commercial software and allows the end user to modify the source codes. The results obtained with the two software match well both qualitatively and quantitatively, demonstrating that OpenFOAM ® is very robust and can be used to simulate complex processes which are relevant in industry.<br
Keywords: Bubble column bio-reactors; numerical simulations; computational Fluid Dynamics

Correction to: A new approach for calculating microalgae culture growth based on an inhibitory effect of the surrounding biomass (Bioprocess and Biosystems Engineering, (2021), 10.1007/s00449-021-02550-6) - Jung, Sun Hwa; McHardy, Christopher; Rauh, Cornelia; Jahn, Alexander; Luzi, Giovanni; Delgado, Antonio; Buchholz, Rainer; Lindenberger, Christoph (Bioprocess and Biosystems Engineering, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s00449-021-02594-8.
CRIS-Team Scopus Importer:2021-06-25

Detection of granular motion using image processing with particular emphasis on rolling motion - Wierschem, Andreas; Rodríguez Agudo, José; Luzi, Giovanni; Han, J.; Hwang, M.; Lee, J. (Review of Scientific Instruments, 2017)
UnivIS-Import:2019-08-15:Pub.2017.tech.ITC.stmmec.detect

Effect of particle size ratio on shear-induced onset of particle motion at low particle Reynolds numbers: From high shielding to roughness - Topic, Nikola; Retzepoglu, S.; Wensing, Michaela; Illigmann, Christian; Luzi, Giovanni; Rodríguez Agudo, José; Wierschem, Andreas (Physics of Fluids, 2019)
We study incipient motion of single beads on regular substrates made of spherical particles of a different size in steady shear flow at small particle Reynolds numbers. We cover a large range of sizes: from small beads that are highly shielded from the shear flow by the substrate spheres, and hence, are susceptible to the flow through the interstices of the substrate, to beads fully exposed to the flow, where the substrate rather acts like roughness of an otherwise flat surface. Numerical and experimental studies agree within measurement uncertainty. To describe the findings, we extend a recently derived model for particles of equal size which was validated over a wide range of substrates [Agudo et al., "Shear-induced incipient motion of a single sphere on uniform substrates at low particle Reynolds numbers," J. Fluid Mech. 825, 284-314 (2017)]. The extended model covers the entire spectrum of size ratios, where the critical Shields number varies from about zero to infinity. The model properly describes the numerical and experimental data. For well exposed beads, we find a scaling law between the critical Shields number and the size ratio between mobile bead and substrate spheres with an exponent of -1.
CRIS-Team Scopus Importer:2019-06-21

Experimental simulation of methane hydrate extraction at high pressure conditions: Influence of the sediment bed - Rodríguez Agudo, José; Park, Jinyoung; Luzi, Giovanni; Williams, Marc; Rauh, Cornelia; Wierschem, Andreas; Delgado, Antonio (Journal of Physics: Conference Series, 2017)
Being a clean alternative to other fossil fuels, Methane Hydrate (MH) is currently considered as one of the most important potential sources for hydrocarbon fuels [1]. In addition, the high energy density of MH and its stability at higher temperatures as compared to LNG (Liquefied Natural Gas) makes MH a potential greener method for energy transportation. At the same time, the low thermodynamic stability of MH strongly questions the future exploitation of gas hydrate deposits, turning its extraction into a possible geohazard [2]. Fluctuations in pressure, temperature, salinity, degree of saturation or sediment bed properties may cause methane gas release from the water lattice. We experimentally study the influence of the sediment bed geometry during formation-dissociation of MH. For this purpose, MH is synthesized within regular substrates in a 93 cm3 high pressure vessel. The regular substrates are triangular and quadratic arrangements of identical glass spheres with a diameter of 2 and 5 mm, respectively. MH formation within regular substrate reduces the possibility of spontaneous nucleation to a unique geometrical configuration. This fact permits us to characterize the kinetics of MH formation-dissociation as a function of the sediment bed geometry. Preliminary experimental results reveal a strong dependence of MH formation on the geometry of the regular substrate. For instance, under the same pressure and temperature, the kinetics of MH production is found to change by a factor 3 solely depending on the substrate symmetry, i.e. triangular or quadrati

Flows due to pressure induced dissociation-formation of gas hydrates - Rodríguez Agudo, José; Kwon, Sinyoung; Saur, Roland; Loekman, Soebiakto; Luzi, Giovanni; Rauh, Cornelia; Wierschem, Andreas; Delgado, Antonio (IOP Conference Series: Materials Science and Engineering, 2017)
During the last decade, Gas Hydrates (GH) have attracted the interest of the scientific community for engineering applications. Carbon dioxide hydrate (CO2H), for instance, may play an important role for capture and sequestration methods in order to reduce global climate change. Despite the extensive literature, the transport phenomena involved during CO2H formation are not yet fully understood. CO2 transfer from gas or liquid phase to the bulk of water is expected to happen not only by molecular diffusion but also driven by natural convective currents induced by CO2 dissolution in water. Using particle tracer methods, we experimentally characterize the flow velocity of the bulk of water during CO2H formation. For that purpose, CO2H is grown inside an optical cell with a volume of 12 mL at various pressures and temperatures. Due to CO2 dissolution, convection currents are noticed prior to hydrate formation. Our experimental results point to a significant correlation between this process and the subsequent hydrate formation. Two well-differentiated hydrate growth patterns were observed depending on the hydrate induction time and the corresponding CO2 concentration distribution inside water. For long induction times, CO2 can be provided from the water phase resulting in rapid growth. Short induction times resulted in slow growth at the interface creating a solid barrier accompanied by a significant drop in the flow velocity. In some cases, the hydrate layer appeared to be unstable and convection could restar

Food technological potentials of CO2 gas hydrate technology for the concentration of selected juices - Seidl, Pia; Loekman, Soebiakto; Sardogan, Miray; Voigt, Erik; Claßen, Timo; Ha, Jawon; Luzi, Giovanni; Sevenich, Robert; Rodríguez Agudo, José; Rauh, Cornelia; Delgado, Antonio (High Pressure Research, 2019)
CO2 gas hydrate technology seems to be a gentle way to concentrate juices, especially comparing to evaporation processes which achieve high levels of concentration and is furthermore energetically favorable in contrast to freeze concentration processes. CO2 can form gas hydrates at around 30–80 bar and 274–283 K. For evaluating this new technology, it is not only important to know the phase equilibrium lines of commercial juices like apple and orange juices but also how the application of e.g. a bubble column affects the gas hydrate formation and separation from the concentrated product. In order to support the experimental outcome, numerical modeling seems suitable to understand the physical background of this novel concentration technology. This includes the simulation of temperature, velocity, pressure and concentration fields using finite volume technique. All three work packages combined will lead to a better understanding of the behavior of gas hydrate technology used to concentrate liquid foo
Keywords: Fruit juice; hydrate technology; food technology; gas hydrate; carbon dioxide/CO2 clathrate; CO2 hydrate

Influence of surface tension and inner pressure on the process of fibre drawing - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Fujimoto Meinecke, Ken; Rauh, Cornelia; Delgado, Antonio (Journal of Lightwave Technology, 2010)
The present contribution deals with thermofluidynamical features occurring during the drawing of capillaries for microstructured optical fibres. Here, the process stability depends strongly on flow and thermal processes taking place as a preform is heated and drawn in the furnace. This is the case particularly for hollow fibres for which the existence of the inner hole directly depends on material parameters such as the surface tension and the rheological properties and on process parameter such as hole internal pressure and the process temperature. A fluid-mechanics model suggested in the literature that makes use of asymptotic analysis based on small aspect ratio of the micro capillaries, has been revisited and improved recently and the leading-order equations have been then examined in some asymptotic limits by Luzi et al.. Starting from the novel class of solutions of the simplified equations of motion the present paper focuses on the effect of both surface tension and internal hole pressure since those are of essential importance during drawing. Thus, comparisons with experimental data are performed, in order to validate the analytical model developed in , which will be briefly presented here. The theoretical model gives very accurate predictions both when the internal hole is pressurized or when no pressure is applied, as long as the temperature does not reach too high values. © 2006 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.ITC.stmmec.influe
Keywords: Asymptotic analysis; Holey fibres; Micro structured optical fibres (MOFs); Numerical methods; Photonic crystal fibres

Numerical analysis of the effects of air on light distribution in a bubble column photobioreactor - McHardy, Christopher; Luzi, Giovanni; Lindenberger, Christoph; Rodríguez Agudo, José; Delgado, Antonio; Rauh, Cornelia (Algal Research, 2018)
Light distribution inside photobioreactors (PBR) is a crucial parameter for the determination of growth of phototropic microorganisms and reactor productivity. In order to compute the light propagation inside PBR, scattering due to the presence of microorganisms is often neglected, since it is difficult to measure experimentally and it is not trivial to handle numerically. Moreover, absorption is usually assumed constant, but it is affected by the concentration of microorganisms and the presence of gas bubbles. In the present contribution we study how the flow hydrodynamics and local gas fractions inside a bubble column PBR affect the light distribution. First, we perform numerical simulations of a bubble column flow at different gas superficial velocities. Afterwards, we use instantaneous air volume fractions to calculate the effective scattering and absorption coefficient of the mixture, as well as the effective scattering phase function. Finally, we compute the polychromatic light distribution inside the PBR by means of a Lattice-Boltzmann solver. On the one hand, we find that gas bubbles affect both spatial distribution and magnitude of the light intensity field and their impact increases at higher gas superficial velocity. On the other hand, we also observe that the biomass counteracts these effects already at concentrations less than 1 kg/m(3) so that the role of the gas phase on light fields seems to be of minor importance in PBR.
Keywords: Bubble column photobioreactor; Numerical simulation; Light distribution; Gas bubbles

Numerical solution and experimental validation of the drawing process of six-hole optical fibers including the effects of inner pressure and surface tension - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Rauh, Cornelia; Fujimoto Meinecke, Ken; Delgado, Antonio (Journal of Lightwave Technology, 2012)
Microstructured optical fibers (MOFs) achieve their desired performance via a pattern of holes that run trough the whole length of the fiber. The variation of the hole pattern allows the production of a variety of optical effects. However, the cross-sectional hole structure can be different from that designed in the preform, due to the combined effects of surface tension and internal pressure. The present paper focuses on the comparison between experiments and numerical calculation of a six hole-optical fiber taking into account the effects of surface tension and internal hole-pressure, since those are of essential importance during drawing. It is shown that the numerical computations deliver reliable results for practical applications and can be used as a predictive tool for fiber development, as long as the inner pressure or the temperature do not exceed too high values. © 2012 IEEE.
UnivIS-Import:2015-03-09:Pub.2012.tech.ITC.stmmec.numeri
Keywords: Hley fibers; microstructured optical fibers (MOFs); nmerical modelling; numerical methods; photonic crystal fibers

Phenomena, mechanisms and structures in wished and unwished foams in matter of biological origin - Gatternig, Bernhard; Osorio Nesme, Anuhar; Almazan Torres, Lidia; Thünnesen, Julian; Beck, Tobias; McHardy, Christopher; Bernstein, Thomas; Luzi, Giovanni; Stahl, Thomas; Rauh, Cornelia; Delgado, Antonio (Proceedings of 2019 World Congress on Advances in Nano, Bio, Robotics, and Energy ANBRE19, 2019)

Potential Application of Innovative Gas Hydrate Technology in Fruit Juices Concentration Process - Loekman, Soebiakto; Claßen, Timo; Seidl, Pia; Luzi, Giovanni; Gatternig, Bernhard; Rauh, Cornelia; Delgado, Antonio (Proceedings of 2019 World Congress on Advances in Nano, Bio, Robotics, and Energy, 2019)

Shear-induced incipient motion of a single sphere on uniform substrates at low particle Reynolds numbers - Rodríguez Agudo, José; Illigmann, Christian; Luzi, Giovanni; Laukart, Artur; Delgado, Antonio; Wierschem, Andreas (Journal of Fluid Mechanics, 2017)

Shear-induced motion of a bead on regular substrates at small particle Reynolds numbers - Topic, Nikola; Rodríguez Agudo, José; Luzi, Giovanni; Czech, Franz; Wierschem, Andreas (Journal of Fluid Mechanics, 2022)
We study experimentally the impact of substrate topology on shear-flow-induced motion of a single bead at low particle Reynolds numbers. The substrates are regular quadratic and triangular arrangements of fixed spherical particles. Their topology is varied by using different spacings between the spheres. Here, we show that it has a strong impact not only on the critical Shields number for incipient bead motion but also on its motion above threshold. We focus on Shields numbers where the bead velocity is smaller than the settling velocity. For the different substrates, the data on the average bead velocity collapse on a master curve, showing the impact of the critical Shields number on the bead motion. To describe the bead motion, we develop a model for creeping flows based on expressions by Goldman, Cox and Brenner for the flow-induced forces and torques on a moving bead near a plane. Our model considers rolling and sliding motion. The bead detaches from the substrate on the downhill side at larger substrate spacing or higher Shields numbers, and flies through the interstices of the substrate until hitting the neighbouring substrate spheres. While sliding has only a minor effect on the average bead velocity, detachment has a strong impact. At large substrate spacings, it leads to a bistability, usually associated with inertial flows, even for adhesionless particles under creeping-flow conditions. The model shows good agreement with the experimental results.
CRIS-Team WoS Importer:2022-08-26

Study of the effects of inner pressure and surface tension on the fibre drawing process with the aid of an analytical asymptotic fibre drawing model and the numerical solution of the full N.-St. equations - Luzi, Giovanni; Epple, Philipp; Rauh, Cornelia; Delgado, Antonio (Archive of Applied Mechanics, 2013)
Micro-structured optical fibres (i.e. fibres that contain holes) have assumed a high profile in recent years and given rise to many novel optical devices. The problem of manufacturing such fibres by heating and then drawing a preform is considered for the case of annular capillaries. A fluid mechanics model suggested in the literature that uses asymptotic analysis based on the small aspect ratio of capillaries has been compared with the full 3D set of the N.-St. equations, for modelling the fabrication of capillaries. The final asymptotic equations, analysed in some asymptotic limits, are solved numerically and then compared with the N.-St. solutions, obtained with a commercial finite elements solver. These asymptotic limits give valuable practical information about the control parameters that influence the drawing process, taking into account the effects of surface tension and inner pressure, since those are of essential importance during drawing. It is shown that the asymptotic method delivers reliable results as long as the inner pressure does not exceed too high values. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2013.tech.ITC.stmmec.studyo
Keywords: Asymptotic analysis; Holey fibres; Mathematical modelling; Micro-structured optical fibres (MOFs); Numerical methods; Photonic crystal fibres

Visually Based Characterization of the Incipient Particle Motion in Regular Substrates: From Laminar to Turbulent Conditions - Rodríguez Agudo, José; Han, Jiwon; Park, Jinyoung; Kwon, Sinyoung; Loekman, Soebiakto; Luzi, Giovanni; Lindenberger, Christoph; Delgado, Antonio; Wierschem, Andreas (Journal of Visualized Experiments, 2018)
Two different experimental methods for determining the threshold of particle motion as a function of geometrical properties of the bed from laminar to turbulent flow conditions are presented. For that purpose, the incipient motion of a single bead is studied on regular substrates that consist of a monolayer of fixed spheres of uniform size that are regularly arranged in triangular and quadratic symmetries. The threshold is characterized by the critical Shields number. The criterion for the onset of motion is defined as the displacement from the original equilibrium position to the neighboring one. The displacement and the mode of motion are identified with an imaging system. The laminar flow is induced using a rotational rheometer with a parallel disk configuration. The shear Reynolds number remains below 1. The turbulent flow is induced in a low-speed wind tunnel with open jet test section. The air velocity is regulated with a frequency converter on the blower fan. The velocity profile is measured with a hot wire probe connected to a hot film anemometer. The shear Reynolds number ranges between 40 and 150. The logarithmic velocity law and the modified wall law presented by Rotta are used to infer the shear velocity from the experimental data. The latter is of special interest when the mobile bead is partially exposed to the turbulent flow in the so-called hydraulically transitional flow regime. The shear stress is estimated at onset of motion. Some illustrative results showing the strong impact of the angle of repose, and the exposure of the bead to shear flow are represented in both regimes.
Keywords: Granular Flow; Particle/Fluid Flow; Sediment Transport; Incipient Motion